Community perceptions on the usage of digital marketing for homestays: the case of Ba'Kealan, Malaysia - Cheuk, Sharon; Atang, Azuriaty; Lo, May Chiun; Ramayah, T. (Universiti Malaysia Sarawak (UNIMAS), 2017)
Rural tourism has become a dynamically developing area in tourism. Apart from developing physical infrastructure, a national priority is to develop ICT in rural areas to improve the local communities’ communications with the outside world. It is believed that with the help of ICT, rural tourism industries have risen up and tourist behaviour, when making purchases for tourism activities, has changed (Buhalis and Law, 2008). In other words, the internet helps tourists and rural destination suppliers to interact and make arrangements. The objective of this study is to examine the perceptions and attitudes of rural homestay owners and other tourism service providers in Ba’kelalan in setting up websites in order to facilitate the promotion of their premises and services. A structured questionnaire was used as a guide to conduct in-depth interviews. Fieldwork was carried out in July 2016 and a total of 7 people were interviewed. The study revealed that homestay owners and other tourism suppliers largely depended on word-of-mouth or direct contact (either via phone calls or emails) for accommodation bookings, and were generally not aware of the potential of digital marketing to promote their businesses. This is a first baseline study on communities’ attitudes towards the usage of digital marketing with respect to their tourism products in this area. The findings will be relevant to future studies of community-based ICT initiatives. Implications from the study and recommendations therefrom are further discussed.